Study of stator slot configuration and coil diameter on BLDC motor efficiency and stability - Hadi Susilo, Sugeng; Yudiyanto, Eko; Rohman, Fatkhur; Wirawan, Wirawan; Adiwidodo, Satworo; Nur Huda, Muhammad Arif; Kurniawan, Bakti Indra; Pebrianti, Dwi; Abas, Mohammad Fadhil (Technology Audit and Production Reserves, 2025)
The object of research is the axial flux BLDC (Brushless DC) motor, widely used in electric vehicles and industrial applications due to its compact design and high efficiency. One of the most problematic areas is optimizing the stator slot configuration and coil diameter to enhance efficiency and stability. Previous studies show that these parameters significantly affect magnetic field distribution, losses, and overall performance. However, a systematic investigation is still needed. Therefore, this study aims to identify optimal parameters to improve BLDC motor efficiency and stability. In the course of the study, an experimental setup with a BLDC motor, controller, power supply, and measurement tool were used. The motor was tested with different stator slots (12 and 24) and coil diameters (0.2 mm, 0.5 mm, 0.7 mm). Measurements included power, current, speed, and temperature. Data analysis assessed the impact on efficiency and stability, supported by numerical simulations for validation and optimization. Received results show that increasing stator slots from 12 to 24 improves magnetic field distribution and motor efficiency, with power output reaching 3060 W in the optimal configuration. This is due to the proposed stator slot variation, which reduces magnetic losses and enhances thermal efficiency. In particular, motors with 24 slots and a 0.5 mm coil diameter achieved the highest efficiency, while a 0.7 mm coil led to performance decline due to increased resistance. The findings highlight the need for an optimal balance between coil diameter and stator slot configuration for stable and efficient operation. This ensures the development of high-performance BLDC motors with improved efficiency and stability. Compared to similar configurations, it offers higher power output, lower magnetic losses, and better thermal regulation. These findings support the advancement of reliable, energy-efficient BLDC motors for electric vehicles and industry, with future research focusing on advanced materials and manufacturing techniques for further optimization